Indeks Konektivitas Eksentrik Edis Pada Graf Annihilator dari Ring Bilangan Bulat Modulo - Risma Amelia; Mohammad Nafie Jauhari; Erna Herawati (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
This study discusses how the general formula of the Ediz eccentric connectivity index (IKEE) in the annihilator graph of the ring of integers modulo. This study aims to determine the Ediz eccentric connectivity index on the annihilator graph of the ring of modular integers , with is a primer number for , and is a positif integer. The initial step in conducting this research is to form an annihilator graph from the ring of integers of the modul , then find the vertex degree and the eccentricity of the vertex on the annihilator graph which is used to calculate the Ediz eccentric connectivity index of each graph. After that, formulate a conjecture about the Ediz eccentric connectivity index on the annihilator graph of the ring of integers of the modul , and the last one proves the hypothesis obtained. The results of this study is general formula for the Ediz eccentric conductivity index on the Annihilator graph of the ring of integers modulo where p is a prime number and m is a positive integer.